El Nino-Southern Oscillation-like variability during glacial terminations and interlatitudinal teleconnections - Pena L. D.; Cacho I.; Ferretti P.; Hall M. A. (Paleoceanography, 2008)
[1] Interannual-decadal variability in the equatorial Pacific El Nino-Southern Oscillation (ENSO) induces climate changes at global scale, but its potential influence during past global climate change is not yet well constrained. New high-resolution eastern equatorial Pacific proxy records of thermocline conditions present new evidence of strong orbital control in ENSO-like variability over the last 275,000 years. Recurrent intervals of saltier thermocline waters are associated with the dominance of La Nina-like conditions during glacial terminations, coinciding with periods of low precession and high obliquity. The parallel dominance of delta(13)C-depleted waters supports the advection of Antarctic origin waters toward the tropical thermocline. This "oceanic tunneling'' is proposed to have reinforced orbitally induced changes in ENSO-like variability, composing a complex high- and low-latitude feedback during glacial terminations.